ANALISIS FAKTORâFAKTOR KETERLAMBATAN DALAM PENYUSUNAN APBD (Studi Kasus di Kabupaten Sukamara) - , Sri Wahyuni ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research was intended to study effect of executive and legislator association, performance indicator, commitment and budget preparation as independent variables on lateness in regional budget preparation as dependent variable. Sample was 58 legislators consisting of budget board, local governmental budget team and member of local government working unit in Sukamara regency to measure effect of independent variable on local budget preparation lateness in Sukamara regency as dependent variable. Results indicated that executive and legislator association, educational background, performance indicator, commitment and budget maker simultaneously affect significantly on local budget making lateness. Partially, executive and legislator association, performance indicator, commitment and budget maker influenced significantly lateness in budget preparation, but the performance indicator has most effect on lateness in budget preparation. The results proved that variables of executive and legislator association, educational background, performance indicator, commitment and budget maker may explain 35.6% variety of change in budget preparation lateness, while the remaining of 64.4% is influenced by variables beyond this research.